Psycholinguistic approaches to instructed second language acquisition linking theory, findings and practice - Walter, Daniel (Multilingual Matters, 2023)
"This book applies a psycholinguistic perspective to instructed second language acquisition, bridging the gap between research and teaching practices. It re-envisions the explicit and implicit learning divide as a continuum of consciousness, explores the pedagogical applications of SLA findings and offers practical suggestions for instructors"--